2019
DOI: 10.15386/mpr-1273
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound appearance of peripheral nerves in the neck: vagus, hypoglossal and greater auricular

Abstract: Background and aim. Information in ultrasonography about reference values of nerves, particularly of those located in the neck is limited. The aim of the study is to demonstrate the feasibility of direct visualization of the vagus, hypoglossal and greater auricular nerves, testing the method on healthy volunteers and estimate the reference values for two perpendicular diameters and cross-sectional area (CSA). Methods. A prospective study was carried out on 21 healthy volunteers (12 women and 9 men), reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 27 publications
7
29
2
Order By: Relevance
“…The left vagus nuclei terminate in the anterior plexus and from there on new branches go to the stomach, liver and the superior part of the abdomen [16,27]. Fourth, the range of the CSA of the vagus nerve we found is similar to previous reports [16,19,25].…”
Section: Discussionsupporting
confidence: 89%
“…The left vagus nuclei terminate in the anterior plexus and from there on new branches go to the stomach, liver and the superior part of the abdomen [16,27]. Fourth, the range of the CSA of the vagus nerve we found is similar to previous reports [16,19,25].…”
Section: Discussionsupporting
confidence: 89%
“…On the aggregate, more studies reported a correlation between BMI and size for different nerves of the upper and lower limbs [ 9 , 11 , 12 , 23 ]. In a recent study published by our group, focused on three nerves of the cervical region, we found a significant correlation for a particular one [ 29 ]. Both the differences between ultrasound and MRI measurements and the variable relationship with BMI may be explained by the measurement technique.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, VN variations were significantly more prevalent in the left side of the neck, with an approximately 10-fold higher proportion of variations compared to the right side (34.7% vs. 3.7%, P<0.001). These findings might be attributable to the left- to right-side difference in the anatomical course of the VN in the thorax and abdomen; moreover, the VN is the only paired nerve that innervates organs in a markedly asymmetric manner [ 13 , 14 ]. In the lower cervical region, the right VN crosses anterior to the right subclavian artery, runs posterior to the superior vena cava, and descends posterior to the right main bronchus.…”
Section: Discussionmentioning
confidence: 99%